Pengaruh Electronic Word Of Mouth (E-Wom), Varian Menu Dan Persepsi Harga Terhadap Keputusan Pembelian Bakso Ummu Akbar Tebing Tinggi - Dea Nirwana Putri; Eni Anggriani; Yenni Arfah; Rajagukguk , Frederick Rudy Sentosa (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to determine the effect of Taste on Purchase Decisions, the effect of Word of Mouth on Purchase Decisions, as well as the simultaneous effect of Taste and Word of Mouth on Purchase Decisions for Mushroom “Larisss” Chicken Noodles. This research uses a quantitative approach. The population in this study consists of all buyers of “larisss” Mushroom Chicken Noodles in Bajenis Subdistrict, Tebing Tinggi City, with the sampling technique using Accidental Sampling and the Cochran formula, resulting in a total of 96 samples. The results of the study found that Taste has a significant positive effect on Purchase Decisions, Word of Mouth has a significant positive effect on Purchase Decisions, and both Taste and Word of Mouth have a significant positive effect simultaneously on Purchase Decisions.